Analysis of Mathematics Education Students' ICT Behavior at IAIN Syekh Nurjati Cirebon Post-Pandemic - Darwan Darwan; Sirojudin Wahid; Shintia Bella Ningtyas (MASI Mandiri Edukasi, 2025)
This study analyzes student behavior in using ICT when using LMS at IAIN Syekh Nurjati Cirebon. This study used quantitative methods with a survey research design. The type of survey used is a cross-sectional survey design. Samples were taken from Mathematics Education students in semesters I, III, V and VII, as many as 258 from 627 active students in 2021/2022 using the stratified random sampling method. The instrument was developed following the aspects and indicators in the TAM model, containing (1) perceived ease of use, (2) perceived usefulness, (3) attitude towards using, (4) behavioral intention to use, and (5) actual usage. The instrument will be tested for validity using CVR and reliability using the Guttman Split-Half Coefficient correlation. Data on student behavior using ICT were analyzed using Widoyoko categorization. The study results showed that the instrument was confirmed to be valid and reliable, with students' behavior in using ICT categorized as